PENGARUH PANDEMIK COVID-19 TERHADAP PARA TENAGA KERJA YANG DI PHK PADA KABUPATEN KARAWANG - Delia Surya Nur Anggraeni; Imam Budi Santoso (Jurnal Ilmiah Advokasi, 2022)
Indonesia is one of the countries affected by the Corona Virus or Covid-19. The Covid-19 pandemic has greatly affected various sectors, especially the employment sector. The problem of unemployment is still a special concern in Indonesia. Karawang Regency is the largest industrial city in Indonesia but in reality there are still many unemployed in Karawang Regency. One of the causes of unemployment is that many companies have terminated their employment during the Covid-19 pandemic due to an emergency (force maeure). The research method carried out at this writing uses normative research methods. The method of collecting information using library research is the method of collecting primary and secondary legal materials. The collection of data contained in books of laws and regulations, literature, magazines and other sources related to daily problems is collected and made into a unified information that is arranged systematically. The results show that the importance of policy reform from the Karawang Regency Government is more effective to overcome the increasing number of unemployed.Keywords: Government; Unemployment; Workers